Impact of urban land cover change on land surface temperature - E. Igun; M. Williams (Global Journal of Environmental Science and Management)
The rapid growth in urban population is seen to create a need for the development of more urban infrastructures. In order to meet this need, natural surfaces such as vegetation are been replaced with non-vegetated surfaces such as asphalt and bricks which has the ability to absorb heat and release it later. This change in land cover is seen to increase the land surface temperature. Previous studies have tried to explain the impact of land cover changes on the land surface temperature. However, there is a growing need to spatially quantify the extent to which temperature has increased so as to identify areas where immediate mitigation measures can be introduced. In view of this, this study has incorporated remotely sensed Landsat data with remote sensing techniques in order to effectively quantify the spatial extent of urban growth and its impact on the land surface temperature in Lagos, Nigeria. The result shows that there have been changes in the land cover which has increased the land surface temperature between 2002 and 2013. Overall, there was an increase in the highly dense areas, moderately dense areas and less dense areas by 3.35% (2200.77 ha), 27.87% (13681.35 ha), 6.20% (3284.01 ha) and a corresponding increase in the mean land surface temperature of these urban areas by 3.8 oC, 4.2 oC and 2.2 oC. Hence, it was recommended that in order to reduce the land surface temperature of urban areas, sustainable urban planning strategies that include increasing the vegetated areas and embracing other green initiatives such as urban forestry should be adopted.